Reflections on the 2019 Canadian Symposium on Academic Integrity - Eaton, Sarah Elaine (Canadian Perspectives on Academic Integrity, 2019)
In this editorial I offer my reflections on the 2019 Canadian Symposium on Academic Integrity, as a co-chair of the event hosted at the University of Calgary, April 18-19, 2019. I consider the origin of the event and consider key learnings. I conclude with a reflection about the impact of the symposium and where we go from here.